The students' preferences on the use of writing strategies at universitas PGRI Wiranegara - Nurjanah, Nanda; Mabaroh, Barotun; Pusparini, Diah Anita (Journal of English Language Proficiency, 2025)
Writing is a crucial skill in English that significantly influences overall language proficiency. The effective use of writing strategies can greatly impact students' writing abilities. This study aimed to explore students' preferences for writing strategies to help lecturers better understand and align their teaching methods with the strategies students tend to use. The research was conducted at Universitas PGRI Wiranegara from June 4th to 24th, 2024, involving 69 English students. The study employed a descriptive quantitative approach, utilizing surveys to gather data on students' writing strategies. The results revealed that most students are familiar with and often apply various strategies during their writing activities. Out of the 35 strategies presented across three different theoretical frameworks, students reported using 33 of them, although not consistently in every writing task. The most commonly used strategy, according to the Likert scale, was "Choosing a topic" from Gail J. Tompkins, with an average score of 4.40, indicating that students usually employ this strategy. In contrast, "Publishing written results online" from the same theorist received a lower average score of 2.68, suggesting that this strategy is only occasionally used. Overall, the findings indicate that students frequently utilize a wide range of writing strategies, with a preference for those proposed by Gail J. Tompkins.